Schools as learning organizations where everyone thrives - Anna Raneri; Antonella Nezzo (IUL Research)
Since the start of the pandemic, keeping the learners at the core of the learning process has assumed an increasing importance, inspiring assessment for learning and learner agency while being connected with the so-called “visible thinking”. But schools are also requested to be learning organizations to cope with change of environment and circumstances, reorganizing the management team to tackle the current situation. The solution has involved creating brand-new middle management roles, meant to support all the teachers while relying on the team members’ skills and the principal’s broader vision and managing expertise. Communication is enhanced and teachers are fully supported, while being nurtured in terms of didactic innovation embedded into lessons, promoting the teachers’tendency to work together, upskilling or reskilling themselves.